Modelling of a passive reactor cavity cooling system (RCCS) for a nuclear reactor core subject to environmental changes and the optimisation of the RCCS radiation heat shield heat shield - Verwey, Aldo (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.